Impact of Different Features of Email on Problem Domain Identification - Rathi, Dinesh (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This study uses a human-machine combined approach to explore the impact of different features of email such as the header, signature, content and reply on clustering. The findings of the study will contribute to the ongoing research in the email domain and help in developing better clustering algorithms to handle noisy email-based data. Cette étude utilise une approche humain-machine combinée pour explorer l’impact de différentes facettes des courriels, par exemple l’en-tête, la signature, le contenu et les réponses, sur l’agrégation. Les résultats contribueront aux travaux en cours sur le courrier électronique et permettront le développement de meilleurs algorithmes d’agrégation capables de traiter le bruit dans les données courriel.